Genus Gelsemium and its Endophytic Fungi - Comprehensive Review of their Traditional Uses, Phytochemistry, Pharmacology, and Toxicology - Peng, Yun-Lin; Liang, Jia-Jun; Xue, Yan; Khan, Afsar; Zhang, Pan-Pan; Feng, Ting-Ting; Song, Da; Zhou, Ying; Wei, Xin (Current Topics in Medicinal Chemistry, 2023)
Background: The use of ethnic medicinal plants has revitalized wide popularity in Africa, Asia, and most of the world because of the energy consumption barriers increase of synthetic drugs. Gelsemium is a traditional genus of plants with famous cultural and medicinal significance in Southeast Asia and North America. Three species are reported from the genus Gelsemium, including Gelsemium elegans (Gardn. & Camp.) Benth., Gelsemium sempervirens (L.) J.St.-Hil., and Gelsemium rankinii Small. Among them, G. elegans is well known for its toxicity and is used as a traditional remedy for skin problems, neuralgia, fractures, and cancer. The first record of the toxic medicine G. elegans is the Chinese herbal medicine classically known as Shen-Nong Ben-Cao Jing. In the legend, the Shennong emperor was poisoned by G. elegans, hence, it is also wellknown as Duan Chang Cao in China. In addition, G. sempervirens tincture is also used in the treatment of inflammation of the spinalcolumn, and diminishes blood to the cerebrospinal centers.Introduction: This review aims to provide up-to-date information on Gelsemium and its endophytic fungi on their traditional uses, phytochemistry, pharmacology, and toxicology. Mechanism studies regarding the detoxification profile of Gelsemium are also reviewed.Methods: For this updated review, the literature survey and search were performed on the scientific databases PubMed, ScienceDirect, Wiley, China CNKI, Web of Science, SciFinder, and Google Scholar using the relevant keywords.Results: The plants of the genus Gelsemium are all reported as rich sources of monoterpene indole alkaloids. Previous phytochemical studies published more than 200 alkaloids from Gelsemium and its endophytic fungi, which have attracted considerable attention from pharmaceutists and phytochemists due to their diverse and complex structures. The bioactivities of Gelsemium phytoconstituents studied using various chemical methods are summarized and described herein. Considering the huge influence of Gelsemium regarding its traditional applications, the activities of isolated compounds were focused on the anti-tumor, anti-inflammatory, analgesic and antianxiety, immunostimulatory, and immunosuppressive properties, which provide evidence supporting the ethnopharmacological effectiveness of the genus Gelsemium. Unlike all previous reviews of genus Gelsemium, to the best of our knowledge, the recently reported natural products from its endophytic fungi are first time summarized in this review.Conclusion: It is clearly suggested from the literature information that the structures and biological activities of Gelsemium have a wide range of attraction from folk to the community of scholars. However, as a highly toxic genus, the work on the detoxification mechanism and toxicology of Gelsemium is urgently needed before entering clinical research. It is noteworthy that the discussion about the relationship between structural and biological activities are a valuable topic of expectation, while the structural modification for active or toxic components may shed light on toxicological breakthrough. Besides the compounds from the plants of genus Gelsemium, the recently reported natural products from its endophytic fungi may provide a supplement for its ethnomedicinal uses and ethnological validity.
Keywords: Endophytic fungi